Pengaruh Harga, Kualitas Produk, Dan Promosi Terhadap Kepuasan Konsumen Studi Kasus Pada PT. Dahlia Dewantara Unit Metro - Nasikah, Durotun; Imantoro, Jati; Putra, Yoga Pratama (Jurnal Manajemen DIVERSIFIKASI, 2023)
Business competition is a competition that must be faced by companies, this increasinglyfierce competition requires companies to be careful in determining strategies to win thecompetition they face. In order to get out of a situation that threatens the life of the company,the company must plan marketing strategies to satisfy consumer desires. Marketing occurs asa social and managerial process by which individuals and groups obtain what they need andwant through creating, offering and exchanging products of value with others. This studyaims to determine 1) To find out whether the price has an effect on consumer satisfaction. 2)To find out whether product quality has an effect on consumer satisfaction. 3) To find outwhether promotion has an effect on consumer satisfaction. 4) To find out whether the priceand product quality variables and promotions together have an effect on consumersatisfaction. This study uses a quantitative approach. The survey method was chosen as theprimary data source. The survey method focuses on collecting data from respondents whohave certain information, thus enabling researchers to solve problems. In this study, thepopulation was taken based on consumers who made purchases of kemplang amandacrackers as many as 75 per month. Data collection techniques using a questionnaire with a Likert scale. The results show that 1) there is a positive and significant influence betweenprice on consumer satisfaction2) there is a positive and significant influence between productquality on consumer satisfaction. 3) there is a positive and significant influence betweenpromotions on consumer satisfaction. 4) there is a positive and significant influence betweenprice, product quality and promotion together on consumer satisfaction